Seasonality and mobility: An Integrative framework for reconstructing Kura-Araxes pastoral systems at Maxta I, Nakhchivan - Gwendoline Maurer; Delphine Frémondeau; Narmin Ismayilova; Safar Ashurov; Veli Bakhshaliyev; Fidan Khalafova Aliyeva; Alexandra Nederbragt; Anne-Lise Jourdan; David Wengrow; Rachel Wood; Louise Martin; Rhiannon E. Stevens (PLoS ONE, 2026)
The Kura-Araxes Culture (3500–2500 BCE) is often depicted as a homogeneous pastoralist horizon, yet its internal economic and mobility strategies remain poorly understood. This study for the first time introduces an integrative framework for reconstructing site-specific pastoral practices through a detailed case study of Maxta I (Nakhchivan). It represents the first study in the Kura-Araxes context and more broadly in the Caucasus to combine zooarchaeology, Zooarchaeology by Mass Spectrometry (ZooMS), stable isotope analysis, and settlement data. This multi-method approach offers a comprehensive view of livestock management, seasonal movement, and socio-economic organisation. The results reveal a seasonally flexible agro-pastoral system that blends permanent settlement features with structured herd mobility, birthing seasons, and possible targeted secondary product exploitation strategies for fleece. Rather than adhering to a binary model of nomadic versus sedentary lifeways, Maxta I demonstrates how Kura-Araxes communities dynamically adapted to diverse ecological and social landscapes. This research challenges assumptions of cultural uniformity and establishes a new comparative model for understanding the diversity of pastoral strategies across Southwest Asia.